2019
DOI: 10.3892/ijo.2019.4867
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia‑induced internalization of connexin 26 and connexin�43 in pulmonary epithelial cells is involved in the occurrence of non‑small cell lung cancer via the P53/MDM2 signaling pathway

Abstract: Reports have highlighted an association between connexins (CXs) or gap junction proteins and non-small cell lung cancer (NSCLC). In the present study, it was aimed to elucidate the regulatory mechanism of CX26 and CX43 under hypoxic conditions in NSCLC. Clinical samples were collected for analysis of CX26 and CX43 expression and clinical cancerization followed by quantification of CX26 and CX43 expression. Following the establishment of an in vitro hypoxia model, P53/murine double minute-2 (MDM2) signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…As shown in Fig. 2B, KEGG pathway enrichment analysis found twelve signi cantly enriched pathways related to cancer progression, such as PI3K-Akt signaling pathway [23,24], ECM-receptor interaction [25,26] and p53 signaling pathway [27,28]. The results indicated that these DEGs played key roles in multiple cancer-related pathways, and further indicated that the DMSs might be involved in LUAD progression by regulating the corresponding gene expression.…”
Section: Functional Enrichment Of Dmgsmentioning
confidence: 84%
“…As shown in Fig. 2B, KEGG pathway enrichment analysis found twelve signi cantly enriched pathways related to cancer progression, such as PI3K-Akt signaling pathway [23,24], ECM-receptor interaction [25,26] and p53 signaling pathway [27,28]. The results indicated that these DEGs played key roles in multiple cancer-related pathways, and further indicated that the DMSs might be involved in LUAD progression by regulating the corresponding gene expression.…”
Section: Functional Enrichment Of Dmgsmentioning
confidence: 84%
“…Western blotting was performed according to a previous description [30]. Briefly, whole cell lysates were normalized by OD600.…”
Section: Western Blottingmentioning
confidence: 99%
“…However, there are very limited published studies concerning the regulatory mechanism of Cx43 during lung cancer development. Hypoxia activates the P53/MDM2 axis and induces Cx43 internalization ( 31 ). Cx43 is moved from the membrane to cytoplasm, where it is degraded ( 31 ), and the lower Cx43 levels promote EMT, inducing proliferation and tumorigenicity in human NSCLC tissue and cells ( 31 ).…”
Section: Primary Lung Cancer and Cxs Expressionmentioning
confidence: 99%
“…Hypoxia activates the P53/MDM2 axis and induces Cx43 internalization ( 31 ). Cx43 is moved from the membrane to cytoplasm, where it is degraded ( 31 ), and the lower Cx43 levels promote EMT, inducing proliferation and tumorigenicity in human NSCLC tissue and cells ( 31 ). In contrast, p38 MAPK activation and JNK inhibition increases Cx43-mediated cell-cell communication via in human lung neoplastic cells and this activation is induced by 4-phenyl-3-butenoic acid ( 32 ).…”
Section: Primary Lung Cancer and Cxs Expressionmentioning
confidence: 99%
See 1 more Smart Citation